The Effect of a Single Session of Eccentric Resistance Exercise on Some Parameters of White Blood Cells - Alireza Ghanbari; Seyed Morteza Tayebi (The Society of Aging and Physical Activity (SAPA), 2013)
It is reported that resistance exercise causes an elevation of white blood cells (WBC) and some of its parameters such as neutrophils (NUT) and lymphocytes (LYM); but there isn't enough study about eccentric exercise (ECC). So, the purpose of this study was to investigate the effect of a single session of eccentric resistance exercise on some parameters of white blood cells. Twelve volunteer male sedentary students were selected to participate in this study. Participants were randomly divided into experimental and control groups. Experimental group performed an eccentric elbow extension (80% of one maximum repetition, 6 sets, 8-10 replicates/sets). Blood sampling implemented at 30 min before the exercise, immediately after the exercise, 2 hours after the exercise, and 24 hours after the exercise. Cell differentiation of WBC for neutrophils (NUT), lymphocytes (LYM), eosinophils (EOS), and monocytes (MON) performed using automated hematology analyzer system [Sysmex (kx-21)]. NUT:LYM ratio was also calculated. It was observed that WBC (F = 9.611, p = 0.001), NUT (F = 9.6, p < 0.001), and LYM (F = 3.28, p < 0.001) increased significantly in response to eccentric exercise, and this elevation continued by 2 hours after the test, while NUT recovered to the initial levels by 24 hours after the exercise, and WBC and LYM remained at a high level at this time. In conclusion, the elevation of WBC immediately after the test is likely due to neutrocytosis and lymphocytosis, but in the recovery period and 24 hours after the exercise is due to lymphocytosis.